Geographic variation in the trophic ecology of an avian rocky shore predator, the African black oystercatcher, along the southern African coastline - (:unkn) unknown (My University, 2011)
The reflection of baseline isotopic signals along marine food chains up to higher trophic levels has been widely used in the study of oceanic top predators but rarely for intertidal predators. We investigated variation in the δ13C and δ15N ratios of a sedentary, rocky shore predator, the African black oystercatcher Haematopus moquini, over ~2000 km of the southern African coastline, which is characterized by strong biogeographic patterns in primary productivity and intertidal communities. Blood and feathers from breeding adults and chicks and muscle tissues from primary prey items (mussels and limpets) were sampled between southern Namibia and the southeast coast of South Africa. 15N enrichment was observed between the southeast and west coasts in oystercatcher tissues and their prey, mirroring an isotope shift between the oligotrophic Agulhas Current on the east coast and the eutrophic Benguela upwelling system on the west coast. Oystercatcher blood showed δ13C values that varied between those of the carbon-depleted mussels and the carbon-enriched limpets along the coastline, which reflected changes in the proportion of grazers and filter feeders in the oystercatcher diet across the sampling range. The geographic shift in diet, dominated by mussels on the west coast and composed of mixed proportions of mussels and limpets on the southeast coasts, strongly reflected regionally high abundances of the invasive Mediterranean mussel Mytilus galloprovincialis. Finally, isotope signatures of blood and feathers displayed a strong correlation throughout the study area, indicating seasonal stability in environmental conditions and feeding habits of the adults. There were, however, local discrepancies on the south coast that indicated movement of adults occurred outside the breeding season possibly in response to a lower abundance of food in this region. Overall, the results indicate that the influence of regional oceanic conditions on the base of the food we
Keywords: African Research